Effect of Modified Atmosphere on Bio-chemical Parameters and Shelf Life of Guava (Psidium guajava L.) cv. Hisar Safeda and L-49 - Bishnoi, Chetak; Sharma, R K; Siddiqui, S (Journal of Postharvest Technology, 2014)
An experiment was conducted to study the effect of different durations of  modified atmosphere on bio-chemical parameters and shelf life of guava under  ambient conditions. Fruits were packed in perforated polyethylene bags  (LDPE) of thickness 300 gauge and then stored at 8ºC in BOD incubator for  the periods 1, 2, 3 and 4 days. After respective durations of storage under MA  at 8ºC, fruits were removed from MA and packed in CFB and stored at  ambient temperature. Fruits were sampled at every day for various bio chemical pigments of guava. Among different durations of MA storage, the  maximum total sugars and reducing sugars was recorded in the fruits stored for  0, 1 and 2 days and minimum in the fruits stored in MA for 4 days. The fruits  stored in MA for different durations maintained high phenol contents and  recorded maximum phenol in the fruit stored in MA for 4 days and minimum  in control fruits. Higher retention of chlorophyll was recorded in the fruits  stored in MA for 4 days while lesser carotenoids were recorded in fruit stored  in MA for 4 days. Carotenoids content increased and chlorophyll content  decreased with the increase in storage period in both the cvs Hisar Safeda and  L-49 (Sardar).
Keywords: Guava; Modified atmosphere Shelf life; Chlorophyll; Carotenoid